Biomarkers of sustained systemic inflammation and microvascular dysfunction associated with post-COVID-19 condition symptoms at 24 months after SARS-CoV-2-infection - Jacobs, Lotte M. C.; Wintjens, Marieke S. J. N.; Nagy, Magdolna; Willems, Loes; ten Cate, Hugo; Spronk, Henri M. H.; van Kuijk, Sander M. J.; Ghossein-Doha, Chahinda; Netea, Mihai G.; Groh, Laszlo A.; van Petersen, André S.; Warlé, Michiel C. (Frontiers in Immunology, 2023)
The aim of this single-centre cohort study was to investigate serum biomarkers of coagulation activation, microvascular dysfunction, and inflammation in relation to symptoms two years after acute COVID-19. Patients diagnosed with acute SARS-CoV-2 infection between February and June 2020 were recruited. Outcome measures included the CORona Follow-Up (CORFU) questionnaire which is based on an internationally developed and partially validated basic questionnaire on persistent symptoms after COVID-19post-COVID-19 condition (PCC) symptoms. Also, plasma biomarkers reflecting coagulation activation, endothelial dysfunction and systemic inflammation were measured. 167 individuals were approached of which 148 (89%) completed the CORFU questionnaire. At 24 months after acute infection, fatigue was the most prevalent post-COVIDPCC symptom (84.5%). Over 50% of patients experienced symptoms related to breathing, cognition, sleep or mobility; 30.3% still experienced at least one severe or extreme (4 or 5 on a 5-point scale) post-COVIDPCC symptom. Multiple correlations were found between several post-COVIDPCC symptoms and markers of endothelial dysfunction (endothelin-1 and von Willebrand factor) and systemic inflammation (Interleukin-1 Receptor antagonist). Additional proteomic analysis revealed an inflammatory signature associated with most of the post-COVID symptoms. No positive correlations were found between post-COVIDPCC symptoms and coagulation complexes. In conclusion, this study shows that at 24 months after acute COVID-19 infection patients experience a high prevalence of post-COVIDPCC symptoms which correlate with an inflammatory signature cytokine IL-1Ra and markers of endothelial dysfunction, especially endothelin-1. Our data may provide a rationale for the selection of treatment strategies for further clinical studies.